Substitution of maize with rice bran and rice polish in the diet of Angora rabbits - BHATT, R S; SHARMA, S R; SINGH, UMESH; BHASIN, V (The Indian Journal of Animal Sciences, 2014)
An experiment was conducted on 30 adult German Angora rabbits, of either sex, divided in to 2 equal groups, to assess the effect of 2 experimental diets (T1 and T2 ), on the biological performance, wool yield, wool characteristics and mortality. Diet T1 consisted of maize - 30%, rice polish - 15%, rice bran - 15%, groundnut-cake - 20%, soyaflakes - 10%, molasses- 8 %, salt - 1 % and mineral mixture - 1 %, whereas in T2 diet, 15% of the maize (i.e.50% of the value in T1) was replaced with rice polish and rice bran (7.5% each). Both diets in mash form were fed, about 150g day-1 head-1 along with wilted grass mixture of rye grass (Lolium perenae), tall fescue (Festuca arundinacea) and white clover (Trifolium repens) ad lib, for a period of 225 days or 3 shearings. Body weights increased in both groups up to second shearing (150 days) and thereafter it decreased due to summer depression. However, final body weight in T1 and T2 were not significantly different from their respective initial body weights. Total dry matter intake (DMI) per animal was significantly (P